The Psychological Experiences of Male Survivors of Sexual Violence - Melvin Takoy; Rizky Pradita Manafe; Feronika Ratu (Universitas Nusa Cendana, 2026)
Sexual violence against men remains underdiscussed and is often marginalized due to prevailing masculinity stigma. This study aims to explore the psychological experiences of male survivors of sexual violence in Kupang City, East Nusa Tenggara. The research employed a qualitative approach using the photovoice method for data collection, involving five male survivors of sexual violence. Thematic analysis identified four main themes. First, the forms of sexual violence experienced included conventional violence (physical, verbal, and non-verbal) as well as digital sexual violence. Second, survivors experienced revictimization through masculinity stigma and barriers to seeking help. Third, survivors’ psychological responses emerged spontaneously across cognitive, affective, and conative domains. Fourth, survivors developed psychological capital in the form of self-efficacy, optimism, and resilience. This study highlights that the psychological experiences of male survivors are complex and shaped by gender norms and social contexts, thus requiring inclusive and gender-sensitive approaches.